Hemisphere-dependent endocannabinoid system activity in prefrontal cortex and hippocampus of the Flinders Sensitive Line rodent model of depression. (May 2019) - Kirkedal, C.; Elfving, B.; Müller, H.K.; Moreira, F.A.; Bindila, L.; Lutz, B.; Wegener, G.; Liebenberg, N.
Abstract: Altered endocannabinoid (eCB) signalling is suggested as an important contributor to the pathophysiology of depression. To further elucidate this, we conducted a study using a genetic rat model of depression, the Flinders Sensitive Line (FSL), and their controls, the Flinders Resistant Line (FRL) rats. Plasma, right and left prefrontal cortex, and hippocampus were isolated from FSL and FRL rats. We analyzed each region for the eCB anandamide (AEA) and 2-arachidonoylglycerol (2-AG) levels by liquid chromatography/multiple reaction monitoring (LC/MRM), mRNA and protein levels of the cannabinoid type 1 receptor (CB1 R), fatty acid amide hydrolase (FAAH) and monoacyl glycerol lipase (MAGL) by real time qPCR and Western blotting. Content of 2-AG was lower in the left side of the hippocampus and prefrontal cortex in FSL rats compared to FRL rats. Inversely, levels of AEA were higher in right hippocampus than in left hippocampus. In plasma, AEA levels were increased and 2-AG decreased. Cannabinoid receptor 1 ( Cnr1 ), Faah and Magl mRNA levels were prominently decreased in right prefrontal cortex of FSL rats as compared to FRL rats. Protein expression of CB1 R and FAAH were decreased in left hippocampus. In summary, our data suggest a decreased eCB signalling in the FSL rats, which could contribute to the depressive-like behaviour. Interestingly, the altered eCB system activity appear to be hemisphere-specific in the limbic regions. Our study support the existing literature and showed altered eCB system activity in this particular animal model of depression. Highlights: Lower levels of 2-AG in left hemisphere of Flinders sensitive Line rats. Inversely related anandamide levels in left and right hippocampus of FSL rats. Incongruence between genetic and protein expression of endocannabinoid components.